The role of adenosine receptor in self-activation in immune cells - Kopicová, Klára (Jihočeská univerzita, 2017)
Adenosine receptor plays very important role in regulation of immune response. Its signalling may lead to initiation of metabolic switch, which suppresses energy consumption by peripheral tissues (selfish behaviour of immunes system). In this thesis I attempt to test the potential role of adenosine signalling in self-activation of immune cells which could alternatively explain its role in systemic energetic switch in model organism Drosophila melanogaster.
The role of adenosine receptor in self-activation in immune cells
Keywords: Extracellular adenosine (e-Ado); adenosine receptor (AdoR); systemic metabolic switch; self-activation of immune cells; Drosophila melanogaster; Leptopilina boulardi; mutant (homozygous; heterozygous) clones; mitotic recombination.; Extracellular adenosine (e-Ado); adenosine receptor (AdoR); systemic metabolic switch; self-activation of immune cells; Drosophila melanogaster; Leptopilina boulardi; mutant (homozygous; heterozygous) clones; mitotic recombination.